Peningkatan Kecakapan Pemecahan Masalah Matematis Siswa Kelas VIII2 SMP Negeri 11 Pekanbaru Melalui Penerapan Model Pembelajaran Kooperatif Metode The Power of Two - Dzahwa Lailatul Najmi; Maimunah Maimunah; Titi Solfitri; Satriani Satriani (Aksioma, 2026)
This study aims to improve students' mathematical problem-solving skills through the implementation of a cooperative learning model using the Power of Two method on the topic of linear equations and inequalities in one variable. The subjects of this study were 36 eighth-grade students from class VIII2 at SMP Negeri 11 Pekanbaru. The research employed a Classroom Action Research (CAR) approach conducted in two cycles, with each cycle consisting of four stages: planning, implementation, observation, and reflection. The instruments used in this study included instructional tools and a mathematical problem-solving ability test (KPMM). The instructional tools consisted of teaching modules, student worksheets (LKS), and formative tests. Data were collected through the KPMM tests and observation sheets documenting the activities of both students and the teacher. Data analysis was carried out using descriptive narrative and statistical techniques. The results of the study indicated that the implementation of the Power of Two method was effective in improving the quality of the learning process and enhancing students' mathematical problem-solving skills. In the first cycle, 2 students achieved scores in the "very good" category, 5 in the "good" category, and 4 in the "fair" category. In the second cycle, there was a significant improvement: 26 students achieved "very good" scores, 10 were in the "good" category, and none were categorized as "fair." This indicates that by the second cycle, students had become accustomed to using the cooperative learning model with the Power of Two method in solving mathematical problems. In conclusion, the implementation of the cooperative learning model using the Power of Two method has been proven to improve the learning process and enhance the mathematical problem-solving abilities of Phase D students in class VIII2 at SMP Negeri 11 Pekanbaru during the odd semester of the 2024/2025 academic year.